A Histopathological Study of Neoplastic Lesions of Conjunctiva - Gupta, Urvashi; Shrestha, Ruchi; Samdurkar, Ashok P; Shahi, Anita (Journal of Universal College of Medical Sciences, 2018)
BACKGROUND: Ocular malignant tumors are relatively rare compared to other eye lesions, require immediate diagnosis and management. But ignorant care due to unawareness of persons can result into debility, loss of vision, and occasionally life is jeopardized.1 The aim of the study is to determine the frequency of most common neoplastc lesions of conjunctiva with histopathologically confirmed diagnosis. MATERIAL AND METHODS: It was a retrospective cross-sectional study done in a period of two years (January 2011 December 2012) that included120 patients who presented with conjunctival lesions to the pathology department of Universal College of Medical Science, Bhairahawa, Nepal. RESULTS: In this study out of 120 biopsies which were histopathologically diagnosed as conjunctival neoplasms were categorized into benign, dysplastic and malignant lesion and was common after second decade of life. Majority of cases (75 cases, 62.5%) were categorized as benign lesion with predominance of squamous papilloma (n=25) and nevus (n=21), followed by malignant lesion (27 cases, 22.5%) and dysplastic lesions (18 cases, 15%). Amongst malignancies, squamous cell carcinoma (SCC) was the most prevalent and a case of malignant melanoma was studied. Dysplastic lesion included conjunctival intraepithelial neoplasia (CIN) with and without squamous papilloma. CONCLUSION: Histopathology plays an important role in diagnosis of conjunctival lesions and rules out different categories of neoplastic lesions on routine basis. In this study Squamous cell carcinoma (SCC) 20.01% is the most common malignant tumor of conjunctiva. The next majority of cases diagnosed as the verrucuous carcinoma 1.66% and malignant melanoma 0.83% maximum case of malignant cases diagnosed in the age group of more than 50 years. Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, Page: 32-35